The effects of ZnGa2O4 formation on structural and optical properties of ZnO : Ga powders - Goncalves, A. D.; de Lima, SAM; Davolos, Marian Rosaly [UNESP]; Antonio, S. G.; Paiva-Santos, CDO (Elsevier B.V., 2006)
Gallium-doped zinc oxide (ZnO:Ga 1, 2 3, 4 and 5 at%) samples were prepared in powder form by modifying the Pechini method. The formation of zinc gallate (ZnGa2O4) With the spinel crystal structure was observed even in ZnO:Ga 1 at% by X-ray diffraction. The presence of ZnGa2O4 in ZnO:Ga samples was also evidenced by luminescence spectroscopy through its blue emission at 430 nm, assigned to charge transfer between Ga3+ at regular octahedral symmetry and its surrounding O2- ions. The amount of ZnGa2O4 increases as the dopant concentration increases, as observed by the quantitative phase analysis by the Rietveld method. (C) 2006 Elsevier B.V. All rights reserved.
Keywords: zinc gallate; impurities in semiconductors; crystal structure and symmetry; optical properties; doping; ZnO : Ga; ZnGa3O4; Pechini method